Exploring healthcare workers’ experiences of a simple intervention to reduce their intrusive memories of psychological trauma: an interpretative phenomenological analysis - Sara Ahmed Pihlgren; Lotta Johansson; Emily A. Holmes; Marie Kanstrup (European Journal of Psychotraumatology, 2024)
ABSTRACTBackground: Many healthcare workers (HCWs) endured psychologically traumatic events at work during the coronavirus disease 2019 (COVID-19) pandemic. For some, these events are re-experienced as unwanted, recurrent, and distressing intrusive memories. Simple psychological support measures are needed to reduce such symptoms of post-traumatic stress in this population. A novel intervention to target intrusive memories, called an imagery-competing task intervention (ICTI), has been developed from the laboratory. The intervention includes a brief memory reminder cue, then a visuospatial task (Tetris® gameplay using mental rotation instructions for approximately 20 min) thought to interfere with the traumatic memory image and reduce its intrusiveness. The intervention has been adapted and evaluated in a randomized controlled trial (RCT) with Swedish HCWs (ClinicalTrials.gov identifier: NCT04460014).Objective: We aimed to explore how HCWs who worked during the COVID-19 pandemic experienced the use of a brief intervention to reduce their intrusive memories of work-related trauma.Method: Interpretative phenomenological analysis was used for in-depth understanding of the lived experiences of HCWs who used the intervention. Seven participants from the RCT were interviewed by an independent researcher without prior knowledge of the intervention. Interviews were conducted via telephone and transcribed verbatim.Results: Four general themes were generated: ‘Triggers and troublesome images’, ‘Five Ws regarding support – what, when, why, by/with who, for whom’, ‘Receiving it, believing it, and doing it’ and ‘The intervention – a different kind of help’; the last two included two subthemes each. The results reflect participants’ similarities and differences in their lived experiences of intrusive memories, support measures, and intervention impressions and effects.Conclusion: HCWs’ experiences of the novel ICTI reflect a promising appraisal of the intervention as a potential help measure for reducing intrusive memories after trauma, and gives us a detailed understanding of HCWs’ needs, with suggestions for its adaption for future implementation.Trial registration: ClinicalTrials.gov identifier: NCT04460014.